Effectiveness of the OPAK Flow Academic Supervision Model (Observation Training Action Collaboration) Based on Microsite in Improving Elementary School Teachers' Pedagogical Competence - Dede Rina Andriani; Lalan Soeherlan; Eka Nurhidayat; Devi Ariyuni Yonanda (Journal of Business, Social and Technology, 2026)
Background: Improving primary education quality depends on teachers’ pedagogical competence, yet conventional academic supervision often fails to produce meaningful changes in classroom practice. Objective: This study examined the effectiveness of the Microsite-based OPAK Flow Academic Supervision Model (Observation, Training, Action, Collaboration) in improving elementary school teachers’ pedagogical competence. Methods: A quasi-experimental nonequivalent control group design was used. Sixty teachers were assigned to an experimental group (n = 30) receiving the OPAK-Microsite intervention or to a control group (n = 30) receiving conventional supervision. Data were analyzed using a paired t-test, an independent-samples t-test, and N-gain scores. Results: The experimental group showed significant improvement (pretest: M = 68.55, SD = 7.21; posttest: M = 85.92, SD= 5.88; t = 14.78, p < 0.001; Cohen’s d = 2.49). The control group showed minimal gains (pretest: M = 67.83; posttest: M= 73.40). Between-group comparison confirmed the superiority of the experimental group (t(58) = 8.34, p < 0.001). Conclusion: The OPAK-Microsite model significantly improves teachers’ pedagogical competence compared to conventional supervision and is recommended for broader implementation.